Isolation of Escherichia coli mutants with changed regulation of uracil uptake. - Fast, R (1978)
The incorporation of uracil into the pyrimidine ribonucleotide pools of Escherichia coli is strongly restricted under stringent conditions. Previously, we have suggested that this inhibition can be explained by the allosteric properties of uracil phosphoribosyltransferase. It has been proposed that this enzyme performs the uptake of uracil into the cell by transporting it across the cytoplasmic membrane, with the stimultaenous formation of UMP. To test this hypothesis it would be helpful to have mutants with changed regulation of uracil uptake, and in the present work, a method is introduced for the selection of such mutants. This method is based on phenotypic suppression of amber mutations by 5-fluorouracil (5FU). Mutants were isolated in an arginine-requiring strain of E. coli carrying an amber mutation in argI, the ornithine transcarbamylase gene. To facilitate the phenotypic rescue of this defective gene, mutants which overproduced ornithine transcarbamylase mRNA were isolated as a first step. The absence of exogenously added arginine causes stringent conditions, and phenotypic rescue by 5FU is, thus, prevented, unless the 5FU uptake mechanism is mutationally changed in such a manner that the drug is taken up into the cell. Three mutants in which the growth could be supported by 5FU in the absence of arginine were isolated. Two of them had acquired an increased ability to take up uracil under stringent conditions.